Freezability and enzyme leakage of crossbred (HF x H) bull semen in 3 dilutors in presence of chlorpromazine HCI - Verma, N K; Kumar, Satish; Mohan, Greesh; Bisht, G S (The Indian Journal of Animal Sciences, 2012)
Effect of 3 buffers (TRIS, MES and TRICINE) and chlorpromazine HCl as an additive on the freezability of half bred (HFxH) bull spemmtozoa using 48 ejaculates (12 each from 4 bulls) were studied. Motility, livability and enzymes (GOT, GPT, ACP and AKP) were estimated in fresh, prefreeze and post-thaw semen. A significant (P